Cricket fast bowling workload patterns as risk factors for tendon, muscle, bone and joint injuries. Issue 16 (9th March 2015) - Orchard, John W; Blanch, Peter; Paoloni, Justin; Kountouris, Alex; Sims, Kevin; Orchard, Jessica J; Brukner, Peter
Abstract : Objective: To assess workload-related risk factors for injuries to particular tissue types in cricket fast bowlers. Design: 235 fast bowlers who bowled in 14600 player innings over a period of 15 years were followed in a prospective cohort risk factor study to compare overs bowled in each match (including preceding workload patterns) and injury risk in the 3–4 weeks subsequent to the match. Injuries were categorised according to the affected tissue type as either: bone stress, tendon injuries, muscle strain or joint injuries. Workload risk factors were examined using binomial logistic regression multivariate analysis, with a forward stepwise procedure requiring a significance of <0.05. Results: High acute match workload and high previous season workload were risk factors for tendon injuries, but high medium term (3-month workload) was protective. For bone stress injuries, high medium term workload and low career workload were risk factors. For joint injuries, high previous season and career workload were risk factors. There was little relationship between muscle injury and workload although high previous season workload was slightly protective. Conclusions: The level of injury risk for some tissue types varies in response to preceding fast bowling workload, with tendon injuries most affected by workload patterns. Workload planning may need to be individualised, depending on individual susceptibility to various injury types. This study supports the theory that tendons are at lowest risk with consistent workloads and susceptible to injury with sudden upgrades in workload. Gradual upgrades are recommended, particularly at the start of a bowler's career to reduce the risk of bone stress injury.